The Impact of Economic Complexity, Usage of Energy, Tourism, and Economic Growth on Carbon Emissions: Empirical Evidence of 102 Countries - Arslan, Aniqa; Qayyum, Arslan; Tabash, Mosab I.; Nair, Kiran; AsadUllah, Muhammad; Nalini Daniel, Linda (International Journal of Energy Economics and Policy, 2023)
This study tries to investigate the impact of economic complexity, usage of energy, tourism, and economic growth on carbon emissions. Economic complexity, economic growth, air travel, and renewable and non-renewable energy consumption have all been the subject of several studies looking at environmental impact on humans. In light of the Environmental Kuznets Curve concept, it is critical to re-evaluate environmental challenges in today’s complex economy. For this purpose, we took the data of 102 countries ranging from 1994 to 2018 and divided such countries into low-income and high-income groups on the basis of GDP per capita. This study applied static models such as pooled, random, and fixed effects. In addition to that, it also applies dynamic model i.e. step-wise system GMM approach for testing the individual and combined effects by controlling for endogeneity. Our results show that tourism has positive and significant impact on carbon emissions. Moreover, the effects are more pronounced for high-income groups. Economic complexity has negative and positive effect on carbon emissions for high-income groups and low-income groups respectively. Moreover, GDP has negative and positive effect on carbon emissions for low-income groups and high-income groups. Our results are consistent by using step-wise system GMM and are robust in nature. Hence, static and dynamic models provide same results with minor differences. This study divides the 102 countries into low-income and high-income groups on the basis of their GDP per capita. It applied static and dynamic models for checking the impact of ecological footprints, economic complexity index, and air travel on environment by supporting Environment Kuznets Curve.